2021
DOI: 10.3390/ijerph181910249
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pesticides and Kidney Function among Adults in the US Population 2001–2010

Abstract: Chronic kidney disease of unknown cause is prevalent in a range of communities; however, its etiology remains unclear. We examined the association between pesticide exposures and the risk of kidney function loss using four waves of the National Health and Nutrition Examination Survey (NHANES) to identify a pathological pathway. We pooled data from four cross-sectional waves of NHANES, with 41,847 participants in total. Exposure to malathion increased the risk of low kidney function (aOR = 1.26, 95% CI = 1.01–1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
9
0
3
Order By: Relevance
“…In Thailand, a study found that rice farmers had significantly lower MCH and MCHC values [ 23 ], whereas other studies have found no difference in the CBC parameters for pesticide-using farmers [ 26 , 27 ]. These inconsistent results may be due to differences in the pesticide type, frequency, and duration in each study, as well as differences in individual immune responses [ 31 ]. Our findings indicated a higher risk of blood disorders such as anemia for vegetable farmers who are repeatedly exposed to pesticides, particularly men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Thailand, a study found that rice farmers had significantly lower MCH and MCHC values [ 23 ], whereas other studies have found no difference in the CBC parameters for pesticide-using farmers [ 26 , 27 ]. These inconsistent results may be due to differences in the pesticide type, frequency, and duration in each study, as well as differences in individual immune responses [ 31 ]. Our findings indicated a higher risk of blood disorders such as anemia for vegetable farmers who are repeatedly exposed to pesticides, particularly men.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature reviews, pesticide exposure is a risk factor for the development of nephrotoxic effects, which include diminished renal function and chronic kidney disease (CKD) [ 28 , 29 , 30 , 31 ]. Exposure to certain pesticides may also increase the risk of end-stage renal disease [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that MT exposure triggers kidney dysfunctions, characterized by alterations of urea, creatinine, TP, and ALB levels and structural modifications in the kidney tissues (Badr 2020 ). On the other hand, organophosphates are implicated in CKD development (Wan et al 2021 ). Hypertension is documented as one of the risk features of CKD (Levey and Coresh 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of previous studies, numerous potential confounding factors that could confound the relationship between OPPs and SHyper have been incorporated into the multivariate model [36][37][38]. The covariate data from the NHANES dataset include age, gender (Male, Female), race (Mexican American, Other Hispanic, Non-Hispanic White, Non-Hispanic Black, Other Race -Including Multi-Racial), body mass index (BMI) (< 25 kg/m2, 25 to < 30 kg/m2, ≥ 30 kg/m2), education level (High school and below, High school and above), family income (< 20,000$, 20,000$ and above), and serum creatinine (mg/dL).…”
Section: Other Variablesmentioning
confidence: 99%